Horizontal and vertical structure of reactive bromine events probed by bromine monoxide MAX-DOAS - Simpson, William R.; Frieß, Udo; Sihler, Holger; Lampel, Johannes; Platt, Ulrich (Atmospheric chemistry and physics, 2017)
Abstract. Heterogeneous photochemistry converts bromide (Br−) to reactive bromine species (Br atoms and bromine monoxide, BrO) that dominate Arctic springtime chemistry. This phenomenon has many impacts such as boundary-layer ozone depletion, mercury oxidation and deposition, and modification of the fate of hydrocarbon species. To study environmental controls on reactive bromine events, the BRomine, Ozone, and Mercury EXperiment (BROMEX) was carried out from early March to mid-April 2012 near Barrow (Utqiaġvik), Alaska. We measured horizontal and vertical gradients in BrO with multiple-axis differential optical absorption spectroscopy (MAX-DOAS) instrumentation at three sites, two mobile and one fixed. During the campaign, a large crack in the sea ice (an open lead) formed pushing one instrument package ∼ 250 km downwind from Barrow (Utqiaġvik). Convection associated with the open lead converted the BrO vertical structure from a surface-based event to a lofted event downwind of the lead influence. The column abundance of BrO downwind of the re-freezing lead was comparable to upwind amounts, indicating direct reactions on frost flowers or open seawater was not a major reactive bromine source. When these three sites were separated by ∼ 30 km length scales of unbroken sea ice, the BrO amount and vertical distributions were highly correlated for most of the time, indicating the horizontal length scales of BrO events were typically larger than ∼ 30 km in the absence of sea ice features. Although BrO amount and vertical distribution were similar between sites most of the time, rapid changes in BrO with edges significantly smaller than this ∼ 30 km length scale episodically transported between the sites, indicating BrO events were large but with sharp edge contrasts. BrO was often found in shallow layers that recycled reactive bromine via heterogeneous reactions on snowpack. Episodically, these surface-based events propagated aloft when aerosol extinction was higher (> 0.1 km−1); however, the presence of aerosol particles aloft was not sufficient to produce BrO aloft. Highly depleted ozone (< 1 nmol mol−1) repartitioned reactive bromine away from BrO and drove BrO events aloft in cases. This work demonstrates the interplay between atmospheric mixing and heterogeneous chemistry that affects the vertical structure and horizontal extent of reactive bromine events.